2021
DOI: 10.1039/d1dt00735a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and proton conductivity studies of fibrous π-Ti2O(PO4)2·2H2O: application in chitosan-based composite membranes

Abstract: Although the fibrous polymorphic modification of titanium phosphate, π-Ti2O(PO4)2·2H2O (π-TiP) is known for decades, its crystal structure has remained unsolved. Herewith we report the crystal structure of π-TiP at a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…S2). [36,37] These nanorods were enriched with stable and homogenously distributed silver nanoparticles (Ag-NPs) that cover their entire surface as was confirmed with the HRTEM, SAED, HAADF and EDX analyses (Fig. 1, Fig.…”
Section: Synthesis Of Nanofibrous Tip Rods and Their Enrichment With ...mentioning
confidence: 61%
See 1 more Smart Citation
“…S2). [36,37] These nanorods were enriched with stable and homogenously distributed silver nanoparticles (Ag-NPs) that cover their entire surface as was confirmed with the HRTEM, SAED, HAADF and EDX analyses (Fig. 1, Fig.…”
Section: Synthesis Of Nanofibrous Tip Rods and Their Enrichment With ...mentioning
confidence: 61%
“…[36] The crystal structure of the π-Ti2O(PO4)2•2H2O (π-TiP) has been very recently solved and its fibrous topology consists of a Ti/P/O framework enclosing linear channels parallel to the direction of fibres growth, containing water molecules coordinated to octahedral-coordinated titanium atoms. [37] Despite its neutral network, π-TiP exhibits ion-exchange properties in aqueous media [38] and its reaction with alkali-metal nitrates results in the formation of fibrous phases. [39] Several studies have reported on the formation of a π-titanium phosphate thin film on a titanium surface using hydrothermal treatment in phosphoric acid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to Ti 3 C 2 T x nanosheets degradation, the hydrothermal derivative of HTOP could be obtained. Compared to the conventional synthesis methods, [24,27,28] Ti 3 C 2 T xderivation provided a more economy and efficiency strategy for TOP fabrication. Finally, different annealing temperature were employed to synthesize TOP@C and carbon coated (TiO) 2 P 2 O 7 (TOPO@C), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1b, after carefully matching, the HTOP is identified as the monoclinic space system with P2 1 /c space group. [27,28] The Rietveld refinement with the standard pattern (PDF#52-1529) of π type Ti 2 O(PO 4 ) 2 •2H 2 O identified that the crystal parameters of HTOP are a = 5.19 Å, b = 14.58 Å, c = 12.05 Å, and β = 114.4°. By contrast with the (020) peak located at ≈12.10 o in the XRD pattern of HTOP, which corresponds to the (002) plane in that of TOP@C due to the crystal transformation induced by the dehydration reaction, [27] shifts to high degree of 12.78 o .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation